Sustaining international careers: a peer group for psychiatrists working in global mental health. (2nd January 2018) - Eaton, Julian; Bouras, Nick; Jones, Lynne; Hanlon, Charlotte; Stewart, Rob; Patel, Vikram
Abstract : Regular appraisal and revalidation are now a routine part of professional life for doctors in the UK. For British-trained psychiatrists working abroad (in either development/humanitarian or academic fields) this is a cause of insecurity, as most of the processes of revalidation are tailored to those working in the standard structures of the National Health Service. This article explores the degree to which a peer group for psychiatrists working abroad has achieved its aim of helping its members to fulfil their revalidation requirements. It gives recommendations for how those considering work abroad can maximise their chances of remaining recognised under the revalidation system.